Pengembangan Video Pembelajaran Ekonomi dengan Aplikasi Kinemaster Pada Pembelajaran Ekonomi - Cakra Binta Suryadi; Rani Sofya (Jurnal Ecogen, 2023)
This study aims to produce a learning video through the stages of development in Economics for high school students.  Research and development (R&D) with the 4D model was chosen as the type of research developed. The results showed that the development of learning video media using the Kinemaster application has passed the validity test, thus the learning video media using the Kinemaster application is valid. used for learning in class X high school economics subjects.  The results of the validity test on learning media products that have been developed are categorized as valid. This is based on the results of media validity with a percentage of 74% and material validity with a percentage of 84%. so that the media developed can be categorized as valid